2015
DOI: 10.1227/neu.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Intracranial Aneurysm Morphology

Abstract: The differences in aneurysm morphology between smoking and nonsmoking patient populations may elucidate the effects of smoking on aneurysm formation and eventual rupture. We identified several aspects of aneurysm morphology significantly associated with smoking status that may provide the morphological basis for how smoking leads to increased aneurysm rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 63 publications
0
21
0
1
Order By: Relevance
“…Furthermore, it was observed in the present study that the diagnosis was delayed in current smokers compared with nonsmokers. In contrast, according to Ho et al, 22 in their study, smokers were diagnosed earlier than nonsmokers. This discrepancy between studies can be explained, at least in part, by the fact that in the present study the number of smokers was small.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, it was observed in the present study that the diagnosis was delayed in current smokers compared with nonsmokers. In contrast, according to Ho et al, 22 in their study, smokers were diagnosed earlier than nonsmokers. This discrepancy between studies can be explained, at least in part, by the fact that in the present study the number of smokers was small.…”
Section: Discussionmentioning
confidence: 55%
“…Because cigarette smoke is a mixture of more than 4000 chemicals, the exact mechanisms by which smoking promotes cerebral aneurysm formation remain largely unknown. 13,19,24 Few studies have evaluated how the outcomes after aneurysmal SAH vary by smoking status. In a single-institution study, Lasner et al found that smoking and Fisher Grade 3 were predictors of symptomatic vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are congruent with the basic research findings that the effects of cigarette smoke on endothelial cells are only functional initially, while the endothelial-cell layer exhibits physical damage and can even be completely destroyed by chronic exposure of cigarette smoke (increase of smoking index) ( 22 ). Moreover, increasing degrees of smoking may be more permissive to accelerate morphological changes of aneurysms ( 23 ). These changes, in turn, may increase the eventual rupture risk of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%